Analisis Faktor Yang Mempengaruhi Perilaku Menyimpang pada Anak di SD Negeri 03 Pakan Labuah - Irawati, Deni; Monia, Fenny Ayu; Puadi , Asral (Indonesian Research Journal on Education, 2023)
This research is motivated by the large number of elementary school-aged children at SD 03 PakanLabuah engages in deviant behavior both outside of school and within the school environment. dealing with deviant behavior in the child. This research is a qualitative descriptive study. Based on the results of the research that has been done, shows that the forms of deviant behavior carried out by children are lying, cheating, being late, scribbling on friends' books, mocking, stealing, and damaging friends' things, making noise, fighting, disturbing friends when learning takes place, and not paying attention to the teacher , not carrying out pickets, fighting teachers, and leaving class without permission. Factors thatinfluence this is due to the inability to absorb cultural norms, deviant learning processes, differences in the social structure between children, family circumstances, and deviant socialization processes. Efforts that must be made to overcome deviant behavior in children are preventive actions, repressive actions, curative actions, and persuasive actions.